Interleukin-8 associated with chemosensitivity and poor chemotherapeutic response to gastric cancer - Sirikan Limpakan (2020)
© 2019 Journal of Gastrointestinal Oncology. Background: Gastric cancer (GC) patients have been found to have developed chemotherapy resistance that has resulted in a lowering of their overall survival rates. Interleukin-6 (IL-6) and interleukin-8 (IL- 8) could be responsible as the predictive biomarkers in monitoring drug resistance. We have developed a protocol to monitor drug treatment by testing ex vivo chemosensitivity and cytokine levels of primary gastric cultures obtained from endoscopic biopsies. Methods: We studied 49 patients with distal GC who underwent primary surgical resection between June 2014 and December 2016 in the northern endemic region of Thailand. The clinical and pathological data of patients were recorded, and the cancer sub-type was classified. The correlation of cytokine IL-6 and IL-8 protein expression levels and chemotherapy sensitivity in primary gastric cultures was investigated. Endoscopic biopsies were collected before and/or after chemotherapy treatment followed by FOLFOXIV regimen (oxaliplatin + 5-FU/leucovorin). The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed to examine ex vivo chemosensitivity to cisplatin, oxaliplatin, 5-fluorouracil (5-FU) and irinotecan. Enzyme-linked immunosorbent assay (ELISA) was performed to investigate cytokine levels. Results: Ex vivo drug treatment of 49 primary gastric cultures from naive patients revealed a significant correlation between basal levels of IL-8 and chemosensitivity to cisplatin (P=0.001) and oxaliplatin (P=0.001). IL-8 protein expression levels were significantly decreased in the early phase after cisplatin and oxaliplatin treatments leading to an increase in cell sensitivity to drug treatments. Among 49 patients, 11 patients were classified as partial or poor responders after drug interventions, in which case, second endoscopic biopsies were performed for determination of chemosensitivity and cytokine levels. The results demonstrated significant decreases in sensitivity to cisplatin (P=0.049) and oxaliplatin (P=0.014), meanwhile IL-8 protein expression levels were significantly increased by P=0.0423 in both drug treatments. There was no correlation of IL-6 and drug resistance when treatments of the primary gastric cultures involved each of the four chemotherapeutic drugs (P=0.0663). Conclusions: Upregulation of IL-8 after drug intervention might be useful as predictive biomarker in monitoring drug resistance in GC patients; however, this needs to be confirmed among a larger number of patients and with control groups that are properly age-paired. The established primary gastric culture could serve as a valuable tool for chemotherapy screening, while the repeated usage of platinum drugs may result in drug resistance via upregulation of IL-8 levels.